Evidence, proof, and fact-finding in WTO dispute settlement - Grando, Michelle T. (Oxford : Oxford University Press, 2010)
This text examines how a World Trade Organization (WTO) dispute settlement panel formulates its conclusions with respect to the facts of a dispute brought before it. It does so by discussing the legal concepts which shape the process of fact-finding, analysing the approach taken by panels thus far and offering suggestions for improvement.
Description based on print version record.
Includes bibliographical references and index.
Keywords: World Trade Organization -- Rules and practice; Dispute resolution (Law); Arbitration, International; Evidence (Law)